ONLINE METACOGNITIVE READING STRATEGIES USE BY LIBYAN SECONDARY SCHOOL STUDENTS (مجلة البحوث الأكاديمية, 2025)
Using internet is popular among students in Libya at different levels these days  , one of the purpose of using internet is online reading , it plays important roles  for EFL readers . Specifically, Libyan students are using different online strategies to understand online reading texts. This study, specifically, aimed to identify the online metacognitive reading strategies used by EFL secondary students in Sirt- Libya and to investigate the relationship between metacognitive online reading strategies and gender among secondary school students in Sirt- Libya.  This study involved 100 secondary school students in Sirt. This study, which is quantitative in nature, is based on an Online Survey of Reading Strategies (OSORS) questionnaire by (Anderson, 2003) and which serves as the research instrument. The findings showed that the sampling were moderate users of metacognitive online reading strategies. Problem solving strategies were the highest frequently used strategies, while global strategies were the least. male students were higher than female students used strategies .Based on the findings, some future research recommendations were presented.